2001
DOI: 10.1016/s0038-1098(01)00229-0
|View full text |Cite
|
Sign up to set email alerts
|

Electric field gradients in MgB2 synthesized at high pressure: 111Cd TDPAC study and ab initio calculation

Abstract: We report the high-pressure synthesis of novel superconductor MgB 2 and some related compounds. The superconducting transition temperature of our samples of MgB 2 is found to be 36.6 K. The MgB 2 lattice parameters determined via X-ray diffraction are in excellent agreement with results of our ab initio calculations. The TDPAC measurements of 111 Cd quadrupole frequency ν Q demonstrate a small increase in ν Q with decreasing temperature from T room to T He .The electric field gradient V zz at the B site calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Finally there is also a report [6] of a negative 11 B shift of mere 5 ppm attributed to the core polarization. These large discrepancies most likely come from the choice of * Electronic address: mali@physik.unizh.ch different materials as references for the Knight shift, as well as from difficulties to measure the small 11 B Knight shift of a broad and in addition quadrupolarly shifted 11 B central line powder spectrum.As far as we know, there are no experimental data concerning the NMR quantities at the Mg site in MgB 2 , although theoretical predictions based on ab initio local density approximation (LDA) calculations exist for Mg Knight shift, 1/T 1 and EFG [7,8]. To some degree the lack of experimental Mg NMR data is understandable considering the fact that the only NMR active 25 Mg isotope has a small magnetic moment and low natural abundance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally there is also a report [6] of a negative 11 B shift of mere 5 ppm attributed to the core polarization. These large discrepancies most likely come from the choice of * Electronic address: mali@physik.unizh.ch different materials as references for the Knight shift, as well as from difficulties to measure the small 11 B Knight shift of a broad and in addition quadrupolarly shifted 11 B central line powder spectrum.As far as we know, there are no experimental data concerning the NMR quantities at the Mg site in MgB 2 , although theoretical predictions based on ab initio local density approximation (LDA) calculations exist for Mg Knight shift, 1/T 1 and EFG [7,8]. To some degree the lack of experimental Mg NMR data is understandable considering the fact that the only NMR active 25 Mg isotope has a small magnetic moment and low natural abundance.…”
mentioning
confidence: 99%
“…As far as we know, there are no experimental data concerning the NMR quantities at the Mg site in MgB 2 , although theoretical predictions based on ab initio local density approximation (LDA) calculations exist for Mg Knight shift, 1/T 1 and EFG [7,8]. To some degree the lack of experimental Mg NMR data is understandable considering the fact that the only NMR active 25 Mg isotope has a small magnetic moment and low natural abundance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27͒ and −3.2 V / Å. 8 In order to investigate the effect of the cell parameters on the calculated EFG, the calculations were repeated with the optimized lattice constants at PW91 level, a = 3.090 Å, and c = 3.584 Å. The difference of calculated EFG with experimental and optimized lattice parameters was smaller than 0.1 V / Å 2 .…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…5 Band structure calculations have shown that Mg atoms are substantially ionized and that the bands at the Fermi level derive mainly from B orbitals. [6][7][8] Hitherto conventional nuclear magnetic resonance ͑NMR͒ studies have been performed on 11 B ͑Refs. 9-13͒ and 25 Mg ͑Refs.…”
Section: Introductionmentioning
confidence: 99%